Inanimate Alice: The Story of the Series and its Impact in Portugal - Ana Maria Machado; Andy Campbell; Ian Harper; Ana Albuquerque e Aguilar; António Oliveira (MatLit, 2018)
A team from the University of Coimbra is partnering with the producers of Inanimate Alice to present a distinctive vision of interactive storytelling in education. In this article, we will discuss the origins of the series, the vision of the creators and how technological developments have added to the user experience. Uniquely, this transmedia narrative demonstrates the progressive complexity of life in the digital age with Perpetual Nomads, the latest adventure, providing a narrative experience in Virtual Reality. The goal of the Portuguese translation is to introduce the reading of Inanimate Alice in elementary and secondary schools. It will be the first digital-born text to be read in Portuguese schools so, concurrently, we have been translating the pedagogical guidelines. Consequently, we intend presenting both the results of our work and the main challenges faced during preparation of the translations, especially focusing on intercultural analysis.